Can we detect rider-related differences in roll and pitch motion of the equine back in professional riders riding the same horses? - Egenvall, A.; Winther Christensen, J.; Munk, R.; Hawson, L.; Roepstorff, L. (11th International Conference International Society for Equitation Science, 2015)
It has been shown that riders affect the health of their horses. It is also known that some riders are more successful in competition than others. However, only some pieces contributing to the rider effect in sport horses have been well demonstrated. To further elucidate the rider effect we investigated whether there we could detect a direct rider effect on the locomotory pattern of horses during riding. Ten professional, female riders each rode 10 dressage horses (level M German scale; n=100 combinations) through a standardised dressage program (10 min warm-up followed by a 5-min test). The experiment was conducted over five days, i.e. each horse was ridden by two riders on each test day. The dressage test was recorded on video. An inertial measurement unit sensor (sampling frequency 256 Hz) was fastened caudal to the saddlepad. For each rider and horse the longest and most complete sequence each of trot, walk, right and left canter were identified. Euler angles were derived from the gyroscopic signals. Roll, the angular motion around the cranio-caudal horizontal axis and pitch, angular motion around left-right horizontal axis were studied. After high-pass filtering, eight ranges of motion (ROM)-measures were constructed for roll and pitch percentile differences [between 98-2, 95-5, 90-10 and 75-10 percentiles], analysed using mixed model analysis with one observation per dyad (including fixed effects of gait, horse and rider with roll analysed in logarithm format). Skewness of roll and pitch were likewise analysed. There was a significant effect of horse (P<0.05) in nine of the 10 models (except the skewness pitch model). The gait effect was significant in all 10 models, and pairwise differences were often found between walk and trot. Rider was significant in five models (98-2 and 95-5 percentiles of roll and pitch and skewness of roll). From pairwise between-rider comparisons it was not evident that differences were due to rider weight. LP: This study found that the angular locomotion of the equine back pattern varied both with rider and horse. That horses have different locomotion patterns was expected but the considerable variation between riders is worth further studies on more horses and riders, as well as the effect of sensors placed also on other body parts of the horse. It is possible that we touched one key to the `rider effect` on performance with possible influence also on health.